POLA KONSUMSI FAST FOOD DAN STATUS GIZI SISWA SEKOLAH DASAR DAERAH PERKOTAAN DAN PEDESAAN - Kadek Yuni Suarsani; Ni Komang Wiardani; Ni Putu Agustini (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2020)
Fast food is favorite food for elementary school students. This study aims to determine the differences in fast food consumption patterns and nutritional status in students in urban and rural areas. This type of research is cross sectional with 69 samples in urban area students and 46 samples in rural area students. Based on the results of the study that in urban area students the consumption of fast food energy is above the average as many as 33 people (47.8%), while in rural areas students are 21 people (45.7%). The frequency of fast food consumption in urban students is 6-7 times a week as many as 42 people (60.9%), while in rural areas students are 1-2 times a week, as many as 33 people (71.7%). The type of fast food that is most often consumed by urban students is Fried Chicken as many as 23 people (33.3%). Whereas in rural areas students were Sausages of 18 people (39.1%). Nutritional status in urban area students namely obesity amounted to 11 people (15.9%). Whereas in rural areas students are obese nutritional status of 2 people (4.3%). After a difference test using Man Whitney, the study showed that there were significant differences between fast food consumption patterns and nutritional status in urban and rural students. Keywords: Fast Food, Nutritional Status, Students